A case with relapsed transient neonatal diabetes mellitus treated with sulfonylurea, ending chronic insulin requirement. (11th April 2018) - Ando, Akihiko; Nagasaka, Shoichiro; Ishibashi, Shun
Summary: We report a case of a woman with diabetes mellitus caused by a genetic defect in ABCC8 -coding sulfonylurea receptor 1 (SUR1), a subunit of the ATP-sensitive potassium (KATP ) channel protein. She was diagnosed with diabetes at 7 days after birth. After intravenous insulin drip for 1 month, her hyperglycaemia remitted. At the age of 13 years, her diabetes relapsed, and after that she had been treated by intensive insulin therapy for 25 years with relatively poor glycaemic control. She was switched to oral sulfonylurea therapy and attained euglycaemia. In addition, her insulin secretory capacity was ameliorated gradually. Learning points: Genetic testing should be considered in any individuals or family with diabetes that occurred within the first year or so of life. Sulfonylurea can achieve good glycaemic control in patients with KATP channel mutations by restoring endogenous insulin secretion, even if they were treated with insulin for decades. Early screening and genetic testing are important to improve the prognosis of patients with neonatal diabetes mellitus arising from ABCC8 or KCNJ11 mutation.